Remote Drying in the North Atlantic as a Common Response to Precessional Changes and CO2 Increase Over Land - Patrick Kelly; Ben Kravitz; Jian Lu; L. Ruby Leung (Geophysical Research Letters)
Abstract Here we demonstrate that changes of the North Atlantic subtropical high and its regional rainfall pattern during mid‐Holocene precessional changes and idealized 4xCO2 increase can both be understood as a remote response to increased land heating near North Africa. Despite different sources and patterns of radiative forcing (increase in CO2 concentration versus changes in orbital parameters), we find that the pattern of energy, circulation, and rainfall responses in the Northern Hemisphere summer subtropics are remarkably similar in the two forcing scenarios because both are dominated by the same land‐sea heating contrast in response to the forcing. An increase in energy input over arid land drives a westward displacement of the coupled North Atlantic subtropical high‐monsoon circulation, consistent with increased precipitation in the Afro‐Asia region and decreased precipitation in the America‐Atlantic region. This study underscores the importance of land heating in dictating remote drying through zonal shifts of the subtropical circulation.